2018
DOI: 10.1177/2047487318770510
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with emotional distress in patients with myocardial infarction: Results from the SWEDEHEART registry

Abstract: BackgroundEmotional distress, symptoms of depression and anxiety, is common among patients after a myocardial infarction (MI), and is associated with an increased risk of cardiovascular morbidity. Real world population data on factors associated with emotional distress in MI patients are scarce. The aim was to determine factors associated with incident emotional distress two and 12 months post MI respectively, and with persistent emotional distress, versus remittent, in patients <75 years old.DesignThis was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 44 publications
2
32
1
2
Order By: Relevance
“…Studies suggest that patient-reported outcomes, such as quality of life and anxiety/depression scores, provide important prognostic information independently of traditional clinical findings and can predict future quality of life, morbidity and mortality in cardiac patients. 11,12 This finding may be explained by both physiological and behavioural processes. 13 A study from Denmark is here demonstrating that patients reporting symptoms of anxiety, depression, poor quality of life and severe symptom distress had a two-fold greater mortality risk, even after adjustment for common cardiovascular risk factors.…”
Section: Patient-reported Outcomes Are Independent Predictors Of One-mentioning
confidence: 92%
“…Studies suggest that patient-reported outcomes, such as quality of life and anxiety/depression scores, provide important prognostic information independently of traditional clinical findings and can predict future quality of life, morbidity and mortality in cardiac patients. 11,12 This finding may be explained by both physiological and behavioural processes. 13 A study from Denmark is here demonstrating that patients reporting symptoms of anxiety, depression, poor quality of life and severe symptom distress had a two-fold greater mortality risk, even after adjustment for common cardiovascular risk factors.…”
Section: Patient-reported Outcomes Are Independent Predictors Of One-mentioning
confidence: 92%
“…Recent large prospective studies have indicated that as many as 38% of patients following their first-time MI experience significant emotional distress within the first 2 months. 11 In this context, the potential WCD patient is approached to consider accepting the WCD and represents a potential psychological dilemma. Does the presence of the WCD provide the patient with a sense of security or does it provide the patient with a reminder of their potential mortality?…”
Section: Psychologicalmentioning
confidence: 99%
“…As one of the most likely consequences of MI, depression is observed in 13% -87% of the patients (6,7). However, recent studies have shown depression is not just induced by acute heart events, but factors such as female gender, younger age, marital status, smoking, hospital stay, fat intake, functional limitation, social support, negative disease beliefs, history of anxiety and depression, and personality traits including type D and neuroticism are involved in it (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%